Common eye diseases in older adults of southern Germany: results from the KORA-Age study - Reitmeir, Peter (Age Ageing, 2017)
PURPOSE: a population-based study in the region of Augsburg (Germany, KORA) was used to identify the prevalence of eye diseases and their risk factors in a sample of aged individuals. METHODS: data originated from the KORA-Age study collected in 2012 and 822 participants (49.6% women, 50.4% men, aged 68–96 years) were asked standardised questions about eye diseases. Positive answers were validated and specified by treating ophthalmologists. Additional information came from laboratory data. Polymorphic markers were tested for candidate genes. RESULTS: we received validations and specifications for 339 participants. The most frequent eye diseases were cataracts (299 cases, 36%), dry eyes (120 cases, 15%), glaucoma (72 cases, 9%) and age-related macular degeneration (AMD) (68 cases, 8%). Almost all participants suffering from glaucoma or from AMD also had cataracts. Cataract surgery was associated with diabetes (in men; OR = 2.24; 95% confidence interval [CI] 1.11–4.53; P = 0.025) and smoking (in women; OR = 6.77; CI 1.62–28.35; P = 0.009). In men, treatments in airway diseases was associated with cataracts (glucocorticoids: OR = 5.29, CI 1.20–23.37; P = 0.028; sympathomimetics: OR = 4.57, CI 1.39–15.00; P = 0.012). Polymorphisms in two genes were associated with AMD (ARMS2: OR = 2.28, CI 1.48–3.51; P = 0.005; CFH: OR = 2.03, CI 1.35–3.06; P = 0.010). CONCLUSION: combinations of eye diseases were frequent at old age. The importance of classical risk factors like diabetes, hypertension and airway diseases decreased either due to a survivor bias leaving healthier survivors in the older age group, or due to an increased influence of other up to now unknown risk factors.